Effectiveness of Laughter Therapy on Reduction of Stress among Nursing Students (Indian Journal of Forensic Medicine & Toxicology, 2020)
Context: Stability of hormones are being effected by consistent stress in the human body which leads tochanges in thoughts and situations that make the individual perplexed, restless or anxious. Laughter therapy isthe antidote for stress. It helps to release serotonin in brain which is essential for the uplift of mood.Aim: The aim of this research is to find out the efficacy of laughter therapy on the decline of stress.Setting and design: Data collection for the commenced study was conducted at Sri Sukhmani College ofNursing and Amar Professional College of Nursing, Dyalpura, District Mohali, Punjab. A quantitative approachwith “Quasi-experimental design” was adopted to conduct this research.Methods and Material: Technique used for selecting the subjects was purposive sampling technique. 60subjects were selected and sub grouped into experimental and control group (30 each). 5 point likert scale i.e.Sheldon Cohen?s (1983) Perceived Stress Scale which includes 10 items, was selected to evaluate the level ofstress among nursing students.Statistical analysis used: Descriptive and inferential statistics were used.Results:• Before implementation of laughter therapy, it was identified that stress scores were approximately samein both the groups.• After implementation of therapy, it was identified that stress scores in the experimental group was lowerthan the control group.Conclusions: Study concluded with the result that stress level is alleviating among student nurses with helpof laughter therapy